Application of regional innovation system aproach in innovation policy analysis in Vietnamese Mekong Delta River - Cao Thi Thu Anh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
Regional innovation policy analysis is a research topic of interest to scholars with many different approaches, this study demonstrates that the regional innovation system approach is appropriate in policy analysis to promote innovation activities in the Mekong Delta River in Vietnam. In this paper, research results were analyzed based on secondary (through research articles, practical reports) and primary (through in-depth interviews with 34 experts, 7 group discussions and 2 case studies in the Mekong Delta River in Vietnam). This study has showed that a regional innovation systems approach can be used for innovation policy analysis in a developing country like Vietnam. This study contributes to deepening the regional innovation system approach in innovation policy analysis and that the application of a regional innovation system approach to promote innovation activities in the Mekong Delta is feasible and practical. Code: 23071401